PENGARUH ASIMETRI INFORMASI DAN KOMITMEN ORGANISASI TERHADAP HUBUNGAN ANTARA PARTISIPASI ANGGARAN DENGAN KESENJANGAN ANGGARAN - Hafsah . (Jurnal Riset AKuntansi dan Bisnis, 2008)
The relationship between budgetary participation and budgetary slack hasbeen examined in several accounting studies with conflicting results. The conflictingresult may reflect the influence of moderating variables. Using a contingencyapproach, this study examines the moderating effects of information asymmetry andorganizational commitment on the relationship between budgetary participation andbudgetary slack.The subjects of this study are responsibility centre managers of go publiccompanies that are located in Sumatera Utara. Mailed questionnaires were used tocollect data. Purposive sampling method used in this study with response rate 53,5%or 61 of 114 questionnaires were sent to responsibility centre managers. ModeratedRegression Analysis (MRA) was used to ascertain the moderating effect in theresearch model. Analysis were based on the responses of 56 responsibility centremanagers.Analysis of interactions between information asymmetry, organizationalcommitment and budgetary participation offered two interesting findings. First, nosiqnificant interactive effect between information asymmetry and budgetaryparticipation were found to have affected budgetary slack. Second, no siqnificantinteractive effect between organizational commitment and budgetary participationwere found to have affected budgetary slack